Estimates of aseismic slip associated with small earthquakes near San Juan Bautista, CA. Issue 11 (9th November 2016) - Hawthorne, J. C.; Simons, M.; Ampuero, J.‐P.
Abstract: Postseismic slip observed after large ( M > 6) earthquakes typically has an equivalent moment of a few tens of percent of the coseismic moment. Some observations of the recurrence intervals of repeating earthquakes suggest that postseismic slip following small ( M ≲ 4 ) earthquakes could be much larger—up to 10 or 100 times the coseismic moment. We use borehole strain data from U.S. Geological Survey strainmeter SJT to analyze deformation in the days before and after 1000 1.9 < M < 5 earthquakes near San Juan Bautista, CA. We find that on average, postseismic strain is roughly equal in magnitude to coseismic strain for the magnitude range considered, suggesting that postseismic moment following these small earthquakes is roughly equal to coseismic moment. This postseismic to coseismic moment ratio is larger than typically observed in earthquakes that rupture through the seismogenic zone but is much smaller than was hypothesized from modeling repeating earthquakes. Our results are consistent with a simple, self‐similar model of earthquakes. Key Points: Observe postseismic strain of small (mostly M<4) earthquakes near San Juan Bautista, CA The 1.5 day postseismic moment is comparable to coseismic moment Observed postseismic to coseismic moment ratio is independent of magnitude